Penguatan Kemampuan Guru dalam Melakukan Riset Ilmiah di SD Muhammadiyah Karangkajen Yogyakarta - Hanif Cahyo Adi Kistoro; Sutarman Sutarman; Abdul Hopid (Communautaire: Journal of Community Service, 2022)
Research is an important activity that must be carried out bya teacher as part of competency development that supportsteaching. The ability of teachers to conduct research variesand not all teachers know, understand and are able to carryout research. This training aims to provide an overview ofthe importance of research and how to implement it. Thistraining is carried out directly using the method of exposureto material and practice. The training participants consistedof 22 principals, vice principals and teachers. trainingactivities include three stages, namely pre-implementation,implementation and evaluation. The results of the trainingfound four important points. First, almost all teachers do notknow and understand how to do research. Second, teachershave so far focused on the field of teaching. Third, teachershave never received training on research. Fourth, mostteachers have never done research. The results of thesefindings are very important to be used as evaluation materialin improving teacher competence in the future. The teacher'shabit of doing research is very supportive in learning such asfinding new strategies that are suitable for application orproviding new material that is relevant to the subject.